2020
DOI: 10.1002/adbi.202000111
|View full text |Cite
|
Sign up to set email alerts
|

Tension Causes Unfolding of Intracellular Vimentin Intermediate Filaments

Abstract: and intermediate filaments (IFs). While the roles of actin-based networks and MT in cell mechanics and cell function have been extensively studied (reviewed, e.g., in refs. [2, 3]), the contribution of IFs to cell mechanics is still relatively opaque, beyond their function in bearing large tensile forces. Of the cytoskeletal proteins, IF constituent proteins have the unique feature of being able to undergo molecular structural changes in response to external loads, at least in vitro, as shown by single-molecul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…In addition to non-physical interactions through biochemical signaling, intermediate filaments also interact with actin filaments through physical contact mediated by cross-linkers, direct binding, and steric effects ( 24 ) as we have previously shown in our in vitro studies ( 44 ). A large portion of VIFs that interact with contractile actin filaments are expected to experience tensile stresses (Figure 1C) ( 49 ). We thus add an element of intermediate filaments in parallel with the actin element, thereby experiencing tensile stresses (Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to non-physical interactions through biochemical signaling, intermediate filaments also interact with actin filaments through physical contact mediated by cross-linkers, direct binding, and steric effects ( 24 ) as we have previously shown in our in vitro studies ( 44 ). A large portion of VIFs that interact with contractile actin filaments are expected to experience tensile stresses (Figure 1C) ( 49 ). We thus add an element of intermediate filaments in parallel with the actin element, thereby experiencing tensile stresses (Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…In relaxed cells, vimentin is in α-helical conformation. In contrast, when cells are under tension, β-sheet conformations are mostly observed [93]. This implies that single filaments display similar mechanical behavior in cells as in vitro.…”
Section: Single Intermediate Filaments Are Flexible and Stretchablementioning
confidence: 96%
“…Recently, non-vibrational spectroscopy experiments have shown the α-to-β sheet conformational change in living cells under different cellular tension [93]. In relaxed cells, vimentin is in α-helical conformation.…”
Section: Single Intermediate Filaments Are Flexible and Stretchablementioning
confidence: 99%
See 1 more Smart Citation
“…These physical effects identified in simplified reconstituted systems likely contribute to mechanical co-dependencies observed in cells, such as toughening by stress dissipation in the vimentin network ( Hu et al, 2019 ), protection against compressive forces by the vimentin network ( Mendez et al, 2014 ), and vimentin-dependent modulation of actin-myosin contractility ( De Pascalis et al, 2018 ). Raman imaging recently showed that actomyosin forces are transmitted to the intermediate filament cytoskeleton: cells on rigid substrates, where myosin contractility is high ( Gupta et al, 2019 ), contained more unfolded vimentin than on soft substrates, where tension is low ( Fleissner et al, 2020 ). In epithelial monolayers a similar mechanical interplay between the actin and intermediate filament networks was found ( Latorre et al, 2018 ), where cell stretching dilutes the actin cortex and hence decreases tension, while keratin filaments that bear tension re-stiffen the cells.…”
Section: Contributions Of Cytoskeletal Crosstalk To Force Transmissio...mentioning
confidence: 99%